Immigrant and Refugee Adolescents’ Resilient Adaptation: Who does well and why? - Motti-Stefanidi, Frosso; Pavlopoulos, Vassilis; Papathanasiou, Nancy; Mastrotheodoros, Stefanos (Psychology: the Journal of the Hellenic Psychological Society, 2020)
Resilient adaptation of immigrant and refugee youth in receiving societies is consequential for the wellbeing of the youth and the prosperity of the receiving societies. Yet there is significant diversity in their adaptation. The central question addressed in this article is: “Who among immigrant and refugee youth do well and why?” To address this question, we present an integrative model for conceptualizing immigrant-youth resilience, which integrates developmental, acculturation, and social psychological perspectives. This resilience framework frames research on the basis of two key questions: First, what challenges immigrant youths’ adaptation? Second, what resources protect their positive adaptation? Accordingly, we present scientific evidence regarding the influence of immigration-specific challenges and contextual and individual-level resources on their positive adaptation. Extant evidence suggests that focusing on strengths and resilience, instead of on weaknesses and psychological symptoms, among immigrant and refugee youth may have significant implications for policy and practice.